2010
DOI: 10.1213/ane.0b013e3181f42fc0
|View full text |Cite
|
Sign up to set email alerts
|

The Different Effects of Midazolam and Propofol Sedation on Dynamic Cerebral Autoregulation

Abstract: Our results suggest that midazolam and propofol sedation have different effects on dynamic cerebral autoregulation despite causing equivalent decreases in steady-state CBF velocity. Only midazolam sedation is likely to improve dynamic cerebral autoregulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(54 citation statements)
references
References 26 publications
3
48
3
Order By: Relevance
“…23 Dynamic cerebral autoregulation is preserved with midazolam sedation, resulting in decreased volatility in intraprocedural cerebral perfusion. 24 While some studies have found that conscious sedation is associated with more rapid reperfusion, our study found no difference in procedure time, time to groin, or time from symptom onset to reperfusion between the general anesthesia and conscious sedation groups. 25,26 Most previously published studies have demonstrated superior outcomes for patients undergoing endovascular recanalization therapy receiving conscious sedation relative to those receiving general anesthesia.…”
Section: Discussioncontrasting
confidence: 79%
“…23 Dynamic cerebral autoregulation is preserved with midazolam sedation, resulting in decreased volatility in intraprocedural cerebral perfusion. 24 While some studies have found that conscious sedation is associated with more rapid reperfusion, our study found no difference in procedure time, time to groin, or time from symptom onset to reperfusion between the general anesthesia and conscious sedation groups. 25,26 Most previously published studies have demonstrated superior outcomes for patients undergoing endovascular recanalization therapy receiving conscious sedation relative to those receiving general anesthesia.…”
Section: Discussioncontrasting
confidence: 79%
“…Indeed, fixing a line through several singular subject MAP/CBF relationships ignores the potential of chronic resetting, e.g., in the case with sustained hypertension [7]. Upon closer examination of the response for CBF (or a related index of CBF) to a change in MAP, recent studies have revealed that this relationship appears to be more pressure passive [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] than previously described. However, the limitations to drawing inferences from the majority of recent studies are threefold.…”
Section: Introductionmentioning
confidence: 99%
“…However, the limitations to drawing inferences from the majority of recent studies are threefold. First, transcranial Doppler ultrasound (TCD) has been widely used to evaluate CBF velocity (CBFV) [8][9][10][11]18,[20][21][22], which accurately represents CBF exclusively in the event that diameter of the insonated vessel remains constant. Whether this is the case with severe decreases or increases in MAP is unclear [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18][19] As a result, it is unlikely that the sedative regime affected AR during this investigation.…”
Section: áHrmentioning
confidence: 89%
“…The CVVHD was performed with citrate anticoagulation in 16 [10][11][12][13][14][15][16][17][18][19][20] min, followed by a measurement time of 45 min. In one patient, the delay was ten minutes, and in two patients, the start of the CVVHD was delayed for more than 60 min (70-290 min) due to technical reasons.…”
Section: Patientsmentioning
confidence: 99%